Effect of DISC1 on the P300 waveform in psychosis. - Shaikh, M; Hall, M; Schulze, K; Dutt, A; Li, K; Williams, I; Walshe, M; Constante, M; Broome, M; Picchioni, M; Toulopoulou, T; Collier, D; et al. (2013)
INTRODUCTION: Abnormalities in the neurophysiological measures P300 amplitude and latency constitute endophenotypes for psychosis. Disrupted-in-Schizophrenia-1 (DISC1) has been proposed as a promising susceptibility gene for schizophrenia, and a previous study has suggested that it is associated with P300 deficits in schizophrenia. METHODS: We examined the role of variation in DISC1 polymorphisms on the P300 endophenotype in a large sample of patients with schizophrenia or psychotic bipolar disorder (n = 149), their unaffected relatives (n = 130), and unrelated healthy controls (n = 208) using linear regression and haplotype analysis. RESULTS: Significant associations between P300 amplitude and latency and DISC1 polymorphisms/haplotypes were found. Those homozygous for the A allele of single-nucleotide polymorphism (SNP) rs821597 displayed significantly reduced P300 amplitudes in comparison with homozygous for the G allele (P = .009) and the heterozygous group (P = .018). Haplotype analysis showed a significant association for DISC1 haplotypes (rs3738401|rs6675281|rs821597|rs821616|rs967244|rs980989) and P300 latency. Haplotype GCGTCG and ACGTTT were associated with shorter latencies. DISCUSSION: The P300 waveform appears to be modulated by variation in individual SNPs and haplotypes of DISC1. Because DISC1 is involved in neurodevelopment, one hypothesis is that disruption in neural connectivity impairs cognitive processes illustrated by P300 deficits observed in this sample.